2003
DOI: 10.3758/bf03195530
|View full text |Cite
|
Sign up to set email alerts
|

On-line simulations of models for backward masking

Abstract: Five simulations of quantitative models of visual backward masking are available on the Internet at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…There are a variety of computational models that account for the existence of both U-shaped and monotonicshaped masking functions (Anbar & Anbar, 1982;Bridgeman, 1971Bridgeman, , 1978Francis, 1997Francis, , 2003Weisstein, 1972). Francis (2000) identified a simple computational principle that accounts for the appearance of a U-shaped masking function and showed that this principle is used by all of these models.…”
Section: U-shaped Backward Maskingmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a variety of computational models that account for the existence of both U-shaped and monotonicshaped masking functions (Anbar & Anbar, 1982;Bridgeman, 1971Bridgeman, , 1978Francis, 1997Francis, , 2003Weisstein, 1972). Francis (2000) identified a simple computational principle that accounts for the appearance of a U-shaped masking function and showed that this principle is used by all of these models.…”
Section: U-shaped Backward Maskingmentioning
confidence: 99%
“…Additional details of the models can be found in Francis (2000) and Francis and Hermens (2002). Simulations of many of the models can be found online, as described in Francis (2003).…”
Section: Model Analysis and Simulationsmentioning
confidence: 99%
“…Durations of target and mask in the current simulations are 1 iteration of inhibition, representing 30msec of real time, except where noted below. The program is that of Francis (2003) , with changes as noted below to simulate novel conditions.…”
Section: Methodsmentioning
confidence: 99%
“…The temporal model of Weisstein (1972) utilizes only six model neurons. On a PC running at 3.2 GHz with 1 GB of RAM, the simulation described in Francis (2003b) takes approximately 29 milliseconds to compute each point in a masking function (there is some variability because it depends on the SOA). A masking function curve such as in Figures 1 or 2 involves calculation of around 10-20 points.…”
Section: Model Structure and Computationmentioning
confidence: 99%
“…Since the turn of the century, there have been even more models. Francis ( 2000 , 2003a , 2003b ) identified a variety of computational systems that could account for many properties of masking. Di Lollo, Enns, and Rensink ( 2000 ) proposed the Computational Model of Object Substitution (CMOS), which nicely fit their experimental findings on common onset masking.…”
mentioning
confidence: 99%